DIGITAL ADVERTISING AND SMART CONSUMPTION: AN ANALYSIS OF CUSTOMER BEHAVIOR AT NUSSABELLA IN LIMA, 2024 - Sagástegui Cruz, Julia Otilia; Aguilar Martinez, Miluska Rocio; Araujo Cieza, Saraí Celmira (LACCEI, 2025)
The objective of this study was to analyze the relationship between digital advertising and consumer buying behavior in the company NussaBella S.A.C., located in Lima Metropolitana during 2024. The research followed a quantitative approach, applied type, with a non-experimental and cross-sectional design. The sample consisted of 100 clients over 18 years old, residing in Lima Metropolitana, who made at least one purchase influenced by the brand’s digital advertising. Surveys were used as the data collection technique, and a questionnaire validated by expert judgment was applied. The results showed a weak and non-significant positive correlation between both variables (Rho = 0.163; p = 0.106). However, significant correlations were found between specific dimensions, suggesting that certain aspects of digital advertising influence stages of the buying process. It is concluded that optimizing such strategies may contribute to enhancing intelligent consumption in digital environments.